2015
DOI: 10.1515/nor-2015-0017
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of Social Media

Abstract: While observers have focused on the political use of social media when exploring their democratic potential, we know little about users' perceptions of these media. These perceptions could well be important to understanding the political use of social media. In exploring users' perceptions, the article asks whether politicians and voters view social media in a similar way, and to what extent they consider social media to be an apt arena for political communication. Within a Norwegian context, which may prove u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 15 publications
0
3
0
2
Order By: Relevance
“…Previous studies (Khoo, ; Stefanone, Lackaff, & Rosen, ) found that youths and women used social media services more frequently. For example, Segaard () found that youths and middle‐aged people are more involved in communicating or expressing themselves via social media compared to older generations. For this reason, we controlled for demographic variables (gender, age, and level of education) in the regression analysis.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Previous studies (Khoo, ; Stefanone, Lackaff, & Rosen, ) found that youths and women used social media services more frequently. For example, Segaard () found that youths and middle‐aged people are more involved in communicating or expressing themselves via social media compared to older generations. For this reason, we controlled for demographic variables (gender, age, and level of education) in the regression analysis.…”
Section: Analysis and Resultsmentioning
confidence: 99%
“…Research has shown that individuals with heavy reliance on the mass media, especially television, are likely to have lower levels of subjective efficacy and, consequently, increased political apathy (Loveless, 2010). Similarly, the way young people perceive media-political content may influence their political behaviour, given the overlapping relationship between perception and people's behaviour (Erubami, 2020;Segaard, 2015). In light of earlier theoretical and empirical findings, we assumed that newspaper exposure would interact significantly with youths' political apathy and their general perception of newspaper content on politics.…”
Section: Political Apathy and Media Usementioning
confidence: 99%
“…Naeste kategori er borgerengagement, som undersøger hvorvidt sociale medier er med til at gøre politikerne mere interaktive, og om sociale medier kan vaere med til at mobilisere nye borgere i stedet for blot at tale til de allerede engagerede. Et tidligt svensk studie baseret på fokusgrupper pointerer, at politikere er mere villige til at indgå i politisk debat end borgere er (Gustafsson 2012), hvilket bekraeftes af et norsk studie (Segaard 2015), som dog finder potentiale for at mobilisere nye borgere på sociale medier. Flere studier konkluderer generelt, at politikere ikke interagerer ofte via sociale medier (Højholt og Kosiara-Pedersen 2011; Graham et al 2013; Klinger 2013; Kalsnes 2016; Jensen 2017).…”
Section: Borgerengagementunclassified